Prevalence of Cardiovascular Comorbidities in Coronavirus Disease 2019, Severe Acute Respiratory Syndrome, and Middle East Respiratory Syndrome: Pooled Analysis of Published Data - Liu, Yang (J Am Heart Assoc, 2020)
BACKGROUND: Coronavirus disease 2019 (COVID‐19) is spreading widely around the world. We conducted this meta‐analysis to explore the prevalence of cardiovascular comorbidities in COVID‐19, severe acute respiratory syndrome (SARS), and Middle East respiratory syndrome (MERS) cases. METHODS AND RESULTS: Relevant reports updated to April 17, 2020, were searched from PubMed, Embase, Web of Science, and the Cochrane Library with no restriction on language. A random‐effects model was used in this meta‐analysis to obtain pooled proportions of cardiovascular comorbidities in COVID‐19, SARS, and MERS. A total of 22 studies (12 for COVID‐19, 4 for SARS, and 6 for MERS) were included in this analysis, and the average age of patients with COVID‐19, SARS, and MERS was 46.41±1.79, 39.16±2.25, and 52.51±4.64 years, respectively. Proportions of cardiovascular comorbidities in coronavirus diseases were as follows: COVID‐19: proportion of hypertension was 17.1% (95% CI, 13.2%–20.9%), proportion of cardiac disease was 4.5% (95% CI, 3.6%–5.5%) and proportion of diabetes mellitus was 8.5% (95% CI, 5.5%–11.4%); SARS: proportion of hypertension was 4.5% (95% CI, 2.0%–7.0%), proportion of cardiac disease was 2.1% (95% CI, 0.6%–3.7%) and proportion of diabetes mellitus was 3.7% (95% CI, 1.0%–6.4%); MERS: proportion of hypertension was 30.3% (95% CI, 18.3%–42.2%), proportion of cardiac disease was 20.9% (95% CI, 10.7%–31.1%), and proportion of diabetes mellitus was 45.4% (95% CI, 27.3%–63.5%). CONCLUSIONS: The prevalence of cardiovascular comorbidities varies among different coronavirus‐associated diseases. With the development of time, proportions of cardiovascular comorbidities in COVID‐19 need further attention.